Why medical schools are tolerant of unethical behavior - Vidal, Edison Iglesias de Oliveira [UNESP]; Silva, Vanessa dos Santos [UNESP]; Santos, Maria Fernanda dos [UNESP]; Jacinto, Alessandro Ferrari [UNESP]; Boas, Paulo José Fortes Villas [UNESP]; Fukushima, Fernanda Bono [UNESP] (Annals Family Medicine, 2015)
The exposure to unethical and unprofessional behavior is thought to play a major role in the declining empathy experienced by medical students during their training. We reflect on the reasons why medical schools are tolerant of unethical behavior of faculty. First, there are barriers to reporting unprofessional behavior within medical schools including fear of retaliation and lack of mechanisms to ensure anonymity. Second, deans and directors do not want to look for unethical behavior in their colleagues. Third, most of us have learned to take disrespectful circumstances in health care institutions for granted. Fourth, the accreditation of medical schools around the world does not usually cover the processes or outcomes associated with fostering ethical behavior in students. Several initiatives promise to change that picture.
Keywords: Medical education; Professional ethics; Professional competence; Empathy